Thrombosis after aortic balloon occlusion during cesarean delivery for abnormally invasive placenta. (February 2018) - Luo, F.; Wu, Z.; Mei, J.; Yue, J.; Yu, X.; Xie, L.
Highlights: Serious complications can occur after aortic balloon occlusion in pregnant women. In our hospital, approximately 10% of patients developed thrombotic complications. All thromboses were treated successfully. Prior to this procedure, the individual risks and benefits should be assessed. Abstract: Background: Abnormally invasive placenta is a major cause of postpartum hemorrhage and cesarean hysterectomy. An increasing number of obstetricians worldwide employ prophylactic aortic balloon occlusion to manage bleeding during cesarean delivery in these patients. However, the safety of this procedure in pregnant women has not been confirmed. Methods: The clinical records of patients who were suspected of having abnormally invasive placenta and who received prophylactic aortic balloon catheterization before cesarean delivery were retrospectively studied for thrombotic complications. Results: There were 121 patients with suspected abnormally invasive placenta who received prophylactic aortic balloon catheterization before surgery and 115 had the balloon inflated during surgery. Twelve of these 121 patients (10%) developed thrombotic complications. Except for one case of venous thrombosis, all other patients exhibited arterial thrombosis in the limbs on the catheterization side and 11 cases (92%) of thrombosis were discovered within 24 hours of delivery. Eventually, eight patients received arterial thromboembolectomy, and four patients received conservative anticoagulation treatment. Conclusion: Aortic balloon occlusion for the management of bleeding in women with an abnormally invasive placenta may not uncommonly result in thrombosis. Therefore, the risks and benefits of the procedure must be carefully weighed before it is utilized in these patients.